Cartilage tissue formation from human adipose-derived stem cells via herbal component (Avocado/soybean unsaponifiables) in scaffold-free culture system - Arefeh Basiri; Batool Hashemibeni; Mohammad Kazemi; Ali Valiani; Maryam Aliakbari; Nazem Ghasemi (Wolters Kluwer Medknow Publications, 2020)
Background: The use of stem cells, growth factors, and scaffolds to repair damaged tissues is a new idea in tissue engineering. The aim of the present study is the investigation of Avocado/soybean (A/S) effects on chondrogenic differentiation of human adipose-derived stem cells (hADSCs) in micromass culture to access cartilage tissue with high quality. Materials and Methods: In this an experimental study After hADSCs characterization, chondrogenic differentiation was induced using transforming growth factor beta 1 (TGF-β1) (10 ng/ml) and different concentrations (5, 10, and 20 μg/ml) of A/S in micromass culture. The efficiency of A/S on specific gene expression (types I, II, and X collagens, SOX9, and aggrecan) was evaluated using quantitative polymerase chain reaction. In addition, histological study was done using hematoxylin and eosin and toluidine blue staining all data were analyzed using one-way analysis of variance (ANOVA) and P ≤ 0.05 was considered to be statistically significant. Results: The results of this study indicated that A/S can promote chondrogenic differentiation in a dose-dependent manner. In particular, 5 ng/ml A/S showed the highest expression of type II collagen, SOX9, and aggrecan which are effective and important markers in chondrogenic differentiation. In addition, the expression of types I and X collagens which are hypertrophic and fibrous factors in chondrogenesis is lower in present of 5 ng/ml A/S compared with TGF-β1 group (P ≤ 0.05). Moreover, the sulfated glycosaminoglycans in the extracellular matrix and the presence of chondrocytes within lacuna were more prominent in 5 ng/ml A/S group than other groups. Conclusion: It can be concluded that A/S similar to TGF-β1 is able to facilitate the chondrogenic differentiation of hADSCs and do not have adverse effects of TGF-β1. Thus, TGF-β1 can be replaced by A/S in the field of tissue engineering.